The Impact of East Java Electricity Investment on the Indonesian Economy: Interregional Input-Output (IRIO) - Aziz, Khalid Fauzi; Taufiqqurrachman, Fahrizal; Arifin, Putri Autika (Universitas Bangka Belitung, 2025)
This study aims to analyze the impact of investment in the electricity sector in East Java using the Interregional Input-Output (IRIO) method. There are several data used for employment data, public income data and IRIO tables sourced from the Central Statistics Agency. The electricity sector is one of the leading sectors in East Java, which shows that it is able to increase the development of the upstream and downstream industries in the electricity sector itself, both directly and indirectly. The influence of the role of electricity sector activities in East Java has made the government's attention to increase electricity investment after the Covid-19 pandemic. The impact of electricity investment on other sectors in East Java occurred in the Mining and Quarrying sector in terms of increasing output and income, the Wholesale and Retail Trade sector; Repair of Motor Vehicles and Motorcycles in terms of increasing the workforce. In addition, it also has an impact on other regions that are the most dominant, namely in South Sumatra and East Kalimantan and the majority still affect other provinces on the island of Java.